Polyethyleneimine and Chitosan Polymer-Based Mucoadhesive Liquid Crystalline Systems Intended for Buccal Drug Delivery - Calixto, Giovana Maria Fioramonti [UNESP]; Victorelli, Francesca Damiani [UNESP]; Dovigo, Lívia Nordi [UNESP]; Chorilli, Marlus [UNESP] (Springer Nature, 2018)
The buccal mucosa is accessible, shows rapid repair, has an excellent blood supply, and shows the absence of the first-pass effect, which makes it a very attractive drug delivery route. However, this route has limitations, mainly due to the continuous secretion of saliva (0.5 to 2 L/day), which may lead to dilution, possible ingestion, and unintentional removal of the active drug. Nanotechnology-based drug delivery systems, such as liquid crystalline systems (LCSs), can increase drug permeation through the mucosa and thereby improve drug delivery. This study aimed at developing and characterizing the mechanical, rheological, and mucoadhesive properties of four liquid crystalline precursor systems (LCPSs) composed of four different aqueous phases (i) water (FW), (ii) chitosan (FC), (iii) polyethyleneimine (FP), or (iv) both polymers (FPC); oleic acid was used as the oil phase, and ethoxylated and propoxylated cetyl alcohol was used as the surfactant. Polarized light microscopy and small-angle X-ray scattering indicated that all LCPSs formed liquid crystalline states after incorporation of saliva. Rheological, texture, and mucoadhesive assays showed that FPC had the most suitable characteristics for buccal application. In vitro release study showed that FPC could act as a controlled drug delivery system. Finally, based on in vitro cytotoxicity data, FPC is a safe buccal drug delivery system for the treatment of several buccal diseases.
Keywords: buccal route; chitosan; drug delivery system; liquid crystalline system; polyethyleneimine